Comparative study of cardiovascular efficiency between the students of Residential Public School and the students of Non Residential Public School at under Sen. Secondary Level. - Solanki, Mr. Ajay (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to compare the cardiovascular efficiency between the students of Residential Public School and the students of Non Residential Public School at under Sen. Secondary Level. Thirty boys student of Residential Public School and thirty boys student of non Residential Public School. The hypothesis that the students of Residential Public School may have better cardiovascular efficiency than the students of Non Residential Public School at the under Sen. Secondary Level was confirmed by the findings of the study.